2020
DOI: 10.2147/ott.s262293
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Noncoding RNA HIF1A-AS2 Promotes Non-Small Cell Lung Cancer Progression by the miR-153-5p/S100A14 Axis</p>

Abstract: Background: Long noncoding RNA (lncRNA) plays a critical role in initiating lung cancer. This study aims to research the function and mechanism of lncRNA HIF1A-AS2 in regulating non-small cell lung cancer (NSCLC) progression. Methods: qRT-PCR was used to analyze gene expression. The CCK-8 assay was performed to detect cell proliferation. The Transwell assay was conducted to examine cell migration and invasion. A Caspase3 activity detection kit was utilized to analyze apoptosis. The luciferase reporter assay wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
(43 reference statements)
0
12
0
1
Order By: Relevance
“…Considering that HIF-1a-AS downregulates the expression of HIF-1a (135) and because HIF-1a plays a role in the progression of cancer, we speculate that SC-144 inhibits the proliferation of ovarian cancer, at least to some extent, via the HIF-1a-AS/HIF-1a axis. However, the function of HIF-1a-AS in malignant tumours is complicated (136,137), and data on the role of HIF-1a-AS in ovarian cancer have not been reported. Hence, future investigation into the function of the HIF-1a-AS/HIF-1a axis in ovarian cancer is recommended (Figure 4).…”
Section: Synthetic Drugsmentioning
confidence: 99%
“…Considering that HIF-1a-AS downregulates the expression of HIF-1a (135) and because HIF-1a plays a role in the progression of cancer, we speculate that SC-144 inhibits the proliferation of ovarian cancer, at least to some extent, via the HIF-1a-AS/HIF-1a axis. However, the function of HIF-1a-AS in malignant tumours is complicated (136,137), and data on the role of HIF-1a-AS in ovarian cancer have not been reported. Hence, future investigation into the function of the HIF-1a-AS/HIF-1a axis in ovarian cancer is recommended (Figure 4).…”
Section: Synthetic Drugsmentioning
confidence: 99%
“…Thus, understanding the molecular mechanism of NSCLC and identifying novel therapeutic targets is of great clinical significance. Zhang et al ( 54 ) reported elevated expression levels of HIF1A-AS2 in NSCLC tissues and cell lines, and this increased expression was associated with a poor prognosis. However, knockdown of HIF1A-AS2 resulted in decreased cell proliferation, migration and invasion, and an increased percentage of apoptotic cells.…”
Section: Expression and Function Of Lncrna Hif1a-as2 In Several Types Of Cancermentioning
confidence: 99%
“…Wu et al ( 14 ) reported that HIF1A-AS2 functions as a protein decoy to inhibit the transcription of PHLDA1 by binding to LSD1, a histone demethylase. Additionally, HIF1A-AS2 acts as a molecular sponge to bind miRNAs to further affect expression of other genes ( 23 , 40 , 50 , 54 , 56 ). Although significant achievements have been obtained with regard to understanding the role of HIF1A-AS2 in various types of cancer, further studies are still required with regard to its regulatory function, as lncRNAs often exhibit several complex regulatory functions/mechanisms.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Interestingly, when the brain is in a hypoxic and ischaemic environment, neurological impairment and neurodegenerative diseases will also have a close relationship with miRNA [4]. Several studies have reported that miR-153-5p has significant anti-tumour effects [7,23]. However, there is no report about the expression characteristic and potential value of miR-153-5p after ischaemic stroke.…”
Section: Introductionmentioning
confidence: 99%